2008
DOI: 10.1016/j.jelectrocard.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of more erratic heart rate patterns is associated with mortality post–myocardial infarction

Abstract: Cardiac patients often have sinus arrhythmia of non-respiratory origin [erratic sinus rhythm" (ESR)]. ESR was quantified using hourly Poincaré and power spectral HRV plots from normal-to-normal interbeat intervals (N-Ns) and hourly values of the short-term fractal scaling exponent and correlations of N-Ns in N=60 non-survivors and N=66 randomly-selected survivors in the Cardiac Arrhythmia Suppression Trial. Hours were coded (ABN) as normal (0), borderline (0.5) or ESR (1). T-tests compared ABN for N=2413 paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 18 publications
5
47
0
Order By: Relevance
“…High NHF power in conjunction with low DFA1 in rehospitalized patients is consistent with the finding of erratic rhythm in relation to poorer outcomes, described by Stein et al17 The presence of an erratic rhythm may misleadingly elevate values of short-term HRV indices, such as HF power 17…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…High NHF power in conjunction with low DFA1 in rehospitalized patients is consistent with the finding of erratic rhythm in relation to poorer outcomes, described by Stein et al17 The presence of an erratic rhythm may misleadingly elevate values of short-term HRV indices, such as HF power 17…”
Section: Discussionsupporting
confidence: 86%
“…Poincaré plots are graphic representations of coordinates corresponding to consecutive normal RR intervals, and were generated for each patient to visualize HRV organization and explore nonlinear HRV characteristics. The Poincaré ratio is the ratio of axes of an ellipse fitted to the plot (SD1= short axis/SD2= long axis, ratio = SD12), reflecting short-term, beat-to-beat variation compared to long-term, continuous variation 7,1517…”
Section: Methodsmentioning
confidence: 99%
“…24,25 Prospective evidence indicates that reductions in HRV are strongly associated with higher incidence of first cardiac events in patients without known cardiovascular disease 26 and predicts the later development of cardiovascular disease. 27,28 Reductions in HRV have therefore been considered a marker for various disease states, most notably a greater risk for cardiovascular disease and all-cause mortality. 29,30 …”
Section: Introductionmentioning
confidence: 99%
“…Heart rate behavior would be erratic if the sinus node, as a receptive end-organ of the neuroautonomic regulatory system, decoupled from the system. 24 Likewise, the increase of HF power, also a measure of vagal activity, in the patient with SND should be interpreted in the same way. Bergfeldt et al found elevated HRV in patients with advanced sick sinus syndrome, 3 and suggested that HRV could be used as a diagnostic or screening measure for SND.…”
Section: Discussionmentioning
confidence: 99%